AKTIVITAS ANTIFUNGI EKSTRAK METANOL DAUN BANDOTAN (Ageratum conyzoides) TERHADAP Phytophthora sp. (Im5) SECARA IN-VITRO - Febia, Ayuni; Mukarlina, Mukarlina; Rahmawati, Rahmawati (Jurnal Protobiont, 2020)
AbstractPhytophthora sp. is a fungus that causes stem rot disease in citrus plants. One of the plants that has antifungal is the leaves of Bandotan (Ageratum conyzoides). This study aims to determine the concentration of methanol extract of Bandotan leaves (A. conyzoides) which is good in inhibiting the growth of isolates of the species Phytophthora sp. (Im5). This study uses a completely randomized design (CRD) with a treatment level consisting of concentrations of 1.5%, 2%, 2.5%, 3% and control. Test for antifungal activity using the poisoning food method. The results showed a concentration of 3% Bandotan leaves methanol extract was the greatest concentration of antifungal activity inhibiting the growth of Phytophthora sp. (Im5).